ATF-DF-WA Algorithm Experimental Code - jinhao zhong (20616116) (2025)
The provided code files serve the following purposes: Preprocess.py – This script handles text preprocessing tasks, such as cleaning and preparing raw text data for further processing. txtvec.py – This script is responsible for text vectorization, converting processed text into numerical representations suitable for machine learning algorithms. stopwords.txt – This file contains the stop words dictionary used in the experiment to remove common words that do not contribute significant meaning to the classification task. classify.py – This script performs text classification using the processed and vectorized data. The threshold value set in the code is 0.1, which effectively enhances the performance of the text classification process.